Bicontinuous cubic phase nanoparticle lipid chemistry affects toxicity in cultured cells. Issue 1 (30th October 2013) - Hinton, Tracey M.; Grusche, Felix; Acharya, Durga; Shukla, Ravi; Bansal, Vipul; Waddington, Lynne J.; Monaghan, Paul; Muir, Benjamin W.
Graphical Abstract: Abstract: Gaining an increased understanding of the toxicity of new lipid nanoparticle formulations such as the class of cubic and hexagonal phase forming nanomaterials called cubosomes™ and hexosomes™ is crucial for their development as therapeutic agents. Surprisingly, the literature on the in vitro and in vivo toxicity of cubic and hexagonal phase forming lipid nanoparticles is negligible, despite a rapidly growing number of publications on their potential use in various therapeutic applications. In this work we have developed methods to study the in vitro cytotoxicity of two chemically distinct cubic phase nanoparticle dispersions using the lipids glycerol monooleate and phytantriol respectively. We have found that the toxicity of phytantriol cubosomes is considerably greater than that of glycerol monooleate cubosomes. The increased toxicity of phytantriol appears to result from its greater ability to disrupt the cellular membrane (haemolytic activity) and oxidative stress. This finding has significant impact and can provide useful guidelines for those conducting further research on the use of cubic phase forming lipids for therapeutic and diagnostic applications both in vitro and in vivo .